Nfat5 is involved in the hyperosmotic regulation of Tmem184b: a putative modulator of ibuprofen transport in renal MDCK I cells - Rune Nørgaard Rasmussen; Kenneth Vielsted Christensen; René Holm; Carsten Uhd Nielsen (FEBS Open Bio, 2019)
Nuclear factor of activated T cells 5 (NFAT5) is a transcription factor involved in the regulation of several genes involved in the response to extracellular hyperosmolality. Recently, the uptake of ibuprofen by an as yet unknown carrier was suggested in Madin‐Darby canine kidney (MDCK) I cells exposed to hyperosmolality. We therefore speculated that Nfat5 could be involved in the regulation of this ibuprofen carrier. Reverse transfection with siRNA against Nfat5 was used to knock down Nfat5 in MDCK I cells. The uptake of both radiolabelled taurine and ibuprofen was measured in MDCK I cells, first treated with siRNA against Nfat5 and afterwards cultivated with raffinose‐supplemented normal growth medium (500 mOsm) for 24 h. The siRNA transfection resulted in knockdown of Nfat5, and uptake of both taurine and ibuprofen was significantly decreased in transfected MDCK I cells. The decrease in ibuprofen uptake indicates that Nfat5 is involved in upregulation of the ibuprofen carrier. A transcriptome analysis of MDCK I cells treated with siRNA against Nfat5 revealed 989 genes upregulated by Nfat5 during hyperosmotic exposure. From these genes, the gene product transmembrane protein 184b was found to be regulated by Nfat5, and Tmem184b was the only potential gene product involved in the uptake of ibuprofen in MDCK I cells. Dataset The RNA sequencing dataset is available from the NCBI Gene Expression 452 Omnibus (https://www.ncbi.nlm.nih.gov/geo/) with the accession number GSE122074.